1975
DOI: 10.1159/000175669
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Dietary Starch and Dietary Sucrose in the Pig

Abstract: Seven litter-mate pairs of male crossbred pigs were fed diets in which 50 % of the dry weight was either corn starch or sucrose for 1 year. Unlike reports of two similar experiments published since our work was carried out, no lesions of the cardiovascular system were found in any of the animals at the end of the experiment. The sucrose-fed animals differed from those fed starch in the following respects: growth was faster during the first 9 weeks of the experiment, but became significantly slower during the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1986
1986
1994
1994

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The lack of effect of sucrose inclusion on serum triglycerides and cholesterol levels is in agreement with previous work (Bruckdorfer and Yudkin, 1975;Waterman, Romsos, Tsai, Miller and Leveille, 1975). This is in contrast to the situation in rats and humans where ingestion of sucrose has been found to result in a rapid rise in blood sugar levels and to give hypertriglyceridaemia (Waterman et al, 1975;Reiser, Hallfrisch, Michaelis, Lazar, Martin and Prather, 1978).…”
Section: Experiments 2: Effect Of Sucrose-based Diets On Growth Carcasupporting
confidence: 92%
See 1 more Smart Citation
“…The lack of effect of sucrose inclusion on serum triglycerides and cholesterol levels is in agreement with previous work (Bruckdorfer and Yudkin, 1975;Waterman, Romsos, Tsai, Miller and Leveille, 1975). This is in contrast to the situation in rats and humans where ingestion of sucrose has been found to result in a rapid rise in blood sugar levels and to give hypertriglyceridaemia (Waterman et al, 1975;Reiser, Hallfrisch, Michaelis, Lazar, Martin and Prather, 1978).…”
Section: Experiments 2: Effect Of Sucrose-based Diets On Growth Carcasupporting
confidence: 92%
“…In pigs, sucrose ingestion also leads to a rapid rise in blood sucrose levels (Rerat et al, 1984a and b). However, pigs do not exhibit a hypertriglyceridaemic or hypercholesterolaemic response to sucrose ingestion (Bruckdorfer and Yudkin, 1975;Waterman et al, 1975). Waterman et al (1975) suggested that species differences in response to sucrose ingestion were related to differences in the major site of triglyceride synthesis.…”
Section: Experiments 2: Effect Of Sucrose-based Diets On Growth Carcamentioning
confidence: 99%
“…Fructose stimulated insulin secretion least. Bruckdorfer and Yudkin (1975) ^Two pigs were used in each of four replicate incubations, and each treatment combination was repeated 3 times per replication. ^An asterisk indicates the location of the radioactive label.…”
Section: Introductionmentioning
confidence: 99%